2021
DOI: 10.3390/atmos12091193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Population Density on CO2 Emissions Eliminating the Influence of Climate

Abstract: More than 50% of the world’s population lives in cities. Its buildings consume more than a third of the energy and generate 40% of the emissions. This makes cities in general and their buildings in particular priority points of attention for policymakers and utilities. This paper uses population density as a variable to know its influence on energy consumption and emissions produced in buildings. Furthermore, to show its effect more clearly, the influence of the climate was eliminated. The usual energy consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…Therefore, for the MINT nations, PD boosts ecological quality. This outcome corroborates the studies of (Meng and Han, 2018;Zarco-Periñán et al, 2021); however, it refutes the studies of (Gyamfi et al, 2022), who found that increasing PD may be a compression in the overall land area and its marginal use, which might increase the EF.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, for the MINT nations, PD boosts ecological quality. This outcome corroborates the studies of (Meng and Han, 2018;Zarco-Periñán et al, 2021); however, it refutes the studies of (Gyamfi et al, 2022), who found that increasing PD may be a compression in the overall land area and its marginal use, which might increase the EF.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…Thus, it is clear that PD and EF nexus have produced mixed findings. For instance, (Zarco-Periñán et al, 2021), scrutinized the role of PD in the mitigation of ecological dilapidation. Population density is used in the research to determine how it affects emissions and energy use from buildings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive coefficients observed in both the short term (0.224) and long term (0.301) suggest that higher population density is correlated with increased GHG emissions, challenging the notion of a simple relationship between population density and environmental quality. This finding is consistent with Zarco-Periñán et al (2021), who found an association between higher population density and increased CO 2 emissions, particularly in urban areas. Similarly, Dimnwobi et al (2021) highlighted the significant role of population growth and density in exacerbating environmental degradation across Africa.…”
Section: Analysis Of Long-run and Short-run Relationships: Cs-ardl Modelsupporting
confidence: 92%
“…When the urban population density is higher, the carbon emissions of energy consumption and heat source emissions of the city will also increase accordingly [59].…”
Section: Ur Urbanization Ratementioning
confidence: 99%